Home in the Poetry of Saudi Arabia Poets: Khalid Al-Faisal an Example of a Distinguished Arab - Yahya Dahami (Hasanuddin University, 2023)
Poetry is the singing of birds, and the homeland is the nest of those birds. Accordingly, we find that there is a mutual link between poetry and the homeland. In order to show the originality and creativity of one of the founders of poetry who loves the homeland, the aim of this research study is to highlight and review some of the values in Saudi poetry. In addition, the study attempts, through critical analysis, to show the status of poetry in the Kingdom of Saudi Arabia, a rapidly growing Arab country that supports contemporary poets and literary giants, in addition to literature, learning, and culture. One of these prominent poets is Khaled Al-Faisal, who devoted his life to the development of the Kingdom of Saudi Arabia and to the production of many styles of contemporary Saudi poetry. It is known that philosophers may express their attachment and belonging through a small part of the larger homeland, and thus they express their love and loyalty to it. On the one hand, the researcher seeks to highlight the poet's experience and show his love for his great homeland, the Kingdom of Saudi Arabia, through the influential poem bearing the title